Dynamics of Paylater Usage in Personal Finance Management: A Bibliometric Study - Loso Judijanto (Sciences du Nord Economics and Business, 2025)
This study explores the evolving academic discourse surrounding Paylater (Buy Now Pay Later) services in the context of personal finance management through a comprehensive bibliometric analysis. Using data from the Scopus database and visualization tools from VOSviewer, the research maps key trends, authorship networks, thematic clusters, and emerging research areas within the literature. The analysis identifies that early studies predominantly focused on technology adoption factors such as ease of use, trust, service quality, and intention to use often framed by models like the Technology Acceptance Model (TAM). Over time, the literature has shifted toward behavioral and psychological aspects, including impulsive buying, financial literacy, and social influence. The co-authorship network reveals a fragmented yet growing scholarly community, while the keyword overlay and heatmaps suggest an increasing focus on consumer behavior and the potential financial risks associated with Paylater use. This study provides a valuable foundation for scholars, practitioners, and policymakers seeking to understand the intellectual structure of the field and to guide future research on the implications of Paylater in personal finance management.